Nigeria Democracy without development: How to fix it - Lesego Motsage (Digital Policy Studies)
Nigeria is a democratic state as well as the wealthiest country in Africa. However, Nigeria is not where the people of the African continent expected it to be twenty years after democracy was instated. The author states, “There is a general assumption that democracy leads to inclusive and sustainable social and economic development” (pg. xxiii). The assumption here is that Nigeria should have witnessed the progressive development characterised by increased infrastructure, employment, equal opportunities for all and high patriotism amongst its citizens rather than the retarded development currently. However, this is not the case for Nigeria; democracy in Nigeria is characterised by corruption, low development, and mismanagement of natural resources. The characteristics mentioned above are why Mr Omano Edigheji saw a need to write this book: he wanted to bring to light the discrepancies within Nigeria’s leadership and why Nigeria has not seen any development in the last two decades lastly, to provide solutions to Nigeria’s problems.